Harnessing the Rhizosphere of the Halophyte Grass Aeluropus littoralis for Halophilic Plant-Growth-Promoting Fungi and Evaluation of Their Biostimulant Activities - Mohamed Tarroum; Walid Ben Romdhane; Ahmed Abdelrahim Mohamed Ali; Fahad Al-Qurainy; Abdullah Al-Doss; Lotfi Fki; Afif Hassairi (Plants, 2021)
Hydroponic systems have gained interest and are increasingly used in hot and dry desert areas. Numbers of benefits are offered by hydroponic systems such as the ability to save water, enhance nutrients use efficiency, easy environmental control, and prevention of soil-borne diseases. However, the high consumption of chemical fertilizers for nutrient solution and the sensitivity of closed hydroponic systems to salinity are issues that need solutions. Thus, the main goal of our research activities is to isolate plant growth promoting fungi in order to develop sustainable hydroponic systems. We are working on isolating and testing the possibility to incorporate the cell-free filtrate (CFF) of plant growth promoting fungi (PGPF) in the composition of the nutrient solution. In this work, we isolated six strains of PGPF from the rhizosphere of the halophyte grass Aeluropus littoralis. Phylogenetic analyses of DNA sequences amplified by ITS1 and ITS4 primers identified the isolated fungi as: Byssochlamys spectabilis, Chaetomium globosum, Cephalotheca foveolata, Penicillium melinii, Alternaria tenuissima, and Nigrospora chinensis. The promoting of vigor in tobacco seedlings was used as criteria to evaluate the biostimulant activity of these fungi by adding either their mycelia (DE: direct effect) or their cell-free filtrates (CFF: indirect effect) to the plant-growth media. The best significant growth stimulation was obtained with plants treated by B. spectabilis. However, only the CFFs of Byssochlamys spectabilis (A5.1) and Penicillium melinii (A8) when added at a dilution factor of 1/50 to half-strength nutritive solution (0.5NS) resulted in significant improvement of all assessed growth parameters. Indeed, the A5.1CFF and A8CFF in 0.5NS induced a significant better increase in the biomass production when compared to NS or 0.5NS alone. All fungi produced indole acetic acid in the CFFs, which could be one of the key factors explaining their biostimulant activities. Furthermore, six genes involved in nitrogen-metabolism (NR1 and NRT1), auxin biosynthesis (Tryp1 and YUCCA6-like), and brassinosteroid biosynthesis (DET2 and DWF4) were shown to be induced in roots or leaves following treatment of plants with the all CFFs. This work opens up a prospect to study in deep the biostimulant activity of PGPFs and their applications to decrease the requirement of chemical fertilizers in the hydroponic growing systems.